Talking to Teens about Pain: A Modified Delphi Study of Adolescent Pain Science Education - Hayley B. Leake; Lauren C. Heathcote; Laura E. Simons; Jennifer Stinson; Steven J. Kamper; Christopher M. Williams; Laura L. Burgoyne; Meredith Craigie; Marjolein Kammers; David Moen; Joshua W. Pate; Kimberley Szeto; et al. (Taylor & Francis Group, 2019)
Background Persistent pain is a prevalent condition that negatively influences physical, emotional, social and family functioning in adolescents. Pain science education is a promising therapy for adults, yet to be thoroughly investigated for persistent pain in adolescents. There is a need to develop suitable curricula for adolescent pain science education. Methods An interdisciplinary meeting of 12 clinicians and researchers was held during March 2018 in Adelaide, South Australia. An a priori objective of the meeting was to identify and gain consensus on key learning objectives for adolescent pain science education using a modified-Delphi process. Results and Conclusion Consensus was reached via a modified Delphi process for seven learning objectives to form the foundation of a curriculum: 1) Pain is a protector; 2) The pain system can become overprotective; 3) Pain is a brain output; 4) Pain is not an accurate marker of tissue state; 5) There are many potential contributors to anyone's pain; 6) We are all bioplastic and; 7) Pain education is treatment. Recommendations are made for promising areas for future research in adolescent pain science education.